Excellent efficacy of trastuzumab deruxtecan in a patient with HER2-positive advanced breast cancer complicated by pulmonary lymphangitic carcinomatosis: a case report and literature review - Luo, Simin; Chai, Jie; Ding, Linxiaoxiao; Tang, Song (Frontiers in Pharmacology, 2025)
Trastuzumab deruxtecan (T-DXd or DS-8201), as a novel antibody–drug conjugate, has demonstrated good efficacy in HER2-positive advanced breast cancer. However, its effectiveness in treating pulmonary lymphangitic carcinomatosis (PLC) has not been previously reported. This paper presents a case of a HER2-positive advanced breast cancer patient who experienced disease progression after treatment with trastuzumab and pertuzumab. The patient developed multiple metastases along with PLC and subsequently received T-DXd treatment, achieving 14.2 months of progression-free survival (PFS). This case is the first to reveal the therapeutic potential of T-DXd in breast cancer patients with PLC.